Protocol of the exploratory prospective observational PEAK study: PrEcision medicine in the management of cardiovascular surgery associated Acute Kidney Injury (AKI) - Uyen Huynh-Do; Jan Waskowski; Nathalie Hammer; Stefan Rudloff; Carmen Pfortmüller; Clarence Pingpoh; Basel Chaikhouni; Sabine Herzig; Myriam Rheinberger; Eva Pedersen; Gere Luder; Drosos Kotelis; et al. (BMJ Open, 2025)
Introduction Acute kidney injury (AKI) due to temporary renal ischaemia is a common, life-threatening complication of many invasive surgical procedures, particularly among the critically ill, frail and elderly. Since no targeted interventions are currently available, innovative strategies for prediction, early detection and personalised treatment of AKI are urgently needed. Based on our results from preclinical renal ischaemia-reperfusion injury models, we postulate that the excess release of cytotoxic calcium phosphate-loaded particles from dying cells and their reuptake by neighbouring cells drive a self-perpetuating necroinflammatory process causing AKI. Furthermore, replenishing the hepatokine fetuin-A, which is rapidly consumed in this process by binding and rendering inert the cellular calcium phosphate debris, can disrupt this vicious cycle. We hypothesise that low plasma levels of fetuin-A are an important patient-specific biomarker associated with AKI and worse clinical outcome after cardiovascular surgery (CVS).Methods and analysis This is a monocentric, prospective, observational study in which the behaviour of fetuin-A in association with frailty and AKI is assessed in 100 patients undergoing elective CVS. The primary objective is to describe the difference between serum fetuin-A at baseline and the day after surgery. Secondary objectives include the description of the course of fetuin-A and a panel of biomarkers with high temporal granularity measured before and during surgery (five time points), and at days 1, 2 and 3 after operation. A potential association of fetuin-A with the occurrence of AKI (at day 7 or discharge) or with chronic kidney disease (at day 90) is investigated. In addition, the Edmonton Frailty Scale (recorded as patient reported outcome measure at baseline and day 90) is used to determine how the degree of frailty affects surgical outcomes. An interim analysis will be conducted after 30 patients have been included.Ethics and dissemination This study was approved by the cantonal ethics committee (Kantonale Ethikkommission) Bern (ID: 2023–02024) and is conducted in accordance with the ethical principles of the Declaration of Helsinki. Results of the study, which will be published in a peer-review journal, will determine whether our aforementioned hypothesis is correct. If so, an established correlation between fetuin-A levels and CVS-associated AKI would facilitate the transitioning of our preclinical work to patient-centred research.Trial registration number NCT06471621.